Criminalistic and criminological features of overcoming counteraction to the investigation of crimes. Stages and chronology of mass riots based on the materials of the Republic of Kazakhstan. - Kurbonov Doniyor Davlat o’g’li (Zien Journals, 2022)
The subject of this study is the description and study of mass riots that took place in the Republic of Kazakhstan. The chronology of mass riots is investigated, the mechanism of crimes committed and their stages are described, the types and classification of ways to counteract the investigation of crimes are determined, as well as methods and means of overcoming counteraction to the investigation of crimes
Keywords: criminalistics; mass riots; the mechanism of committing a crime; overcoming counteraction